2018
DOI: 10.12678/1089-313x.22.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mirror Feedback and Ankle Joint Laxity on Dynamic Balance in Trained Ballet Dancers

Abstract: Enhanced understanding of dynamic postural stability (DPS) has the potential to curtail lower extremity injuries with important implications for athletic and scientific populations. The ability to stabilize following dynamic tasks such as jumping is dependent on several intrinsic factors, including ligamentous laxity, proprioception, and neuromuscular control. Ballet dancers are a unique group of aesthetic performers who frequently must perform unipedal balance during dynamic tasks. The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Additionally, requiring a specific forward focus forces the dancer to rely more on proprioception in order to accurately identify where each spoke is rather than looking where their foot is going, which closely mimics a more dance-specific environment. 8,28,33,44,45 The upper-body restrictions created a more dance-specific protocol that did not inhibit the dancer's ability to reach maximally, as demonstrated by no significant differences in the reach distance or COP values achieved between the dsSEBT parallel, dsSEBT turnout, and the oSEBT conditions. This suggests that the dsSEBT parallel or turnout conditions could be used as a baseline measurement of dancer's balance capabil-ities without the need for the dancer to complete the oSEBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, requiring a specific forward focus forces the dancer to rely more on proprioception in order to accurately identify where each spoke is rather than looking where their foot is going, which closely mimics a more dance-specific environment. 8,28,33,44,45 The upper-body restrictions created a more dance-specific protocol that did not inhibit the dancer's ability to reach maximally, as demonstrated by no significant differences in the reach distance or COP values achieved between the dsSEBT parallel, dsSEBT turnout, and the oSEBT conditions. This suggests that the dsSEBT parallel or turnout conditions could be used as a baseline measurement of dancer's balance capabil-ities without the need for the dancer to complete the oSEBT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The ability to achieve static and dynamic stability while maintaining sufficient range of motion in specific joints to give aesthetic lines is an important unique technique requirement for most dance styles that is not necessarily required for most other sports. [4][5][6][7][8] Often, the focal point of ballet and contemporary dance movements is the non-weightbearing extremity or gesture limb; therefore, upper body and torso compensations must be kept to a minimum so as not to be distracting. 7,9,10 In addition to performing movements on one leg, other movements common in most dance genres, such as jumps, require balance and stability to land efficiently functionally as well as aesthetically.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the lower ankle stiffness under VD could be that missed visual inputs impede information transmission, which activates the muscles ( McKeon and Hertel, 2008 ; Ibrahim and Abdallah, 2020 ). Miller et al (2018) have further reported the importance of visual feedback, which may allow users to receive external joint position cueing, which is also conducive to sending the protection strategy’s activation signal. The motion system subsequently manipulates ankle positioning and stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, increasing hip flexion to increase ΔL by deepening squat range might be an effective precaution in reducing injury risk in the unstable extremity during drop landing. Miller et al (2018) have found that individuals with lower ankle stiffness would utilize a more protective landing strategy that increases hip and knee flexion to provide stability for an uncertain landing.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…38 To date, research examining balance in dance has used a range of measurement tools, 23,[52][53][54][55][56] but to our knowledge only three studies employed a dynamic-movement-to-static-state tool using TTS protocols. 19,20,57 Timeto-stabilization is considered to be a more functionally relevant measure than static-based assessments for athletic populations, 58,59 and dynamic measures have been developed to more closely replicate athletic performance, including reducing the time given to stablize. 39 This TTS force-platemeasure is defined as the time required to stabilize quickly to a static state over the base of support after a jump-landing task.…”
Section: Functional Relevancementioning
confidence: 99%